2003
DOI: 10.1152/jn.01116.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Properties and Ionic Signature of Neuronal Progenitors of the Postnatal Subventricular Zone In Situ

Abstract: Previous studies have reported the presence of neuronal progenitors in the subventricular zone (SVZ) and rostral migratory stream (RMS) of the postnatal mammalian brain. Although many studies have examined the survival and migration of progenitors after transplantation and the factors influencing their proliferation or differentiation, no information is available on the electrophysiological properties of these progenitors in a near-intact environment. Thus we performed whole cell and cell-attached patch-clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
71
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 56 publications
(82 reference statements)
14
71
0
Order By: Relevance
“…Proliferating cells concentrated on the lateral CG belonged to clusters electrically and metabolically coupled via Cx43. The bipolar morphology and expression of BLBP indicated that these cells represent a subtype of RGs (Pinto and Götz, 2007) with electrophysiological properties similar to precursors found in neurogenic zones of the forebrain (Noctor et al, 2002;Filippov et al, 2003;Wang et al, 2003;Liu et al, 2006). The expression of Pax6 supports the persistence of postnatal neurogenic domains, a property that may be related with the remarkable ability of low vertebrates to recover after spinal cord injury.…”
Section: Discussionmentioning
confidence: 71%
“…Proliferating cells concentrated on the lateral CG belonged to clusters electrically and metabolically coupled via Cx43. The bipolar morphology and expression of BLBP indicated that these cells represent a subtype of RGs (Pinto and Götz, 2007) with electrophysiological properties similar to precursors found in neurogenic zones of the forebrain (Noctor et al, 2002;Filippov et al, 2003;Wang et al, 2003;Liu et al, 2006). The expression of Pax6 supports the persistence of postnatal neurogenic domains, a property that may be related with the remarkable ability of low vertebrates to recover after spinal cord injury.…”
Section: Discussionmentioning
confidence: 71%
“…13a,b, available at www.jneurosci.org as supplemental material). New GCs acquired the ability to fire action potentials when the right balance between sodium and potassium currents was reached (Ͻ1 wpi) (see also Carleton et al, 2003;Wang et al, 2003). Soon after (ϳ2 wpi), we found that newborn neurons form the first functional GABAergic synapses with mitral cells.…”
Section: Time Course Of the Functional Integration Of New Neuronsmentioning
confidence: 73%
“…In mature neurons, this channel opens primarily in response to the depolarization provided by excitatory synaptic inputs (Weisskopf et al, 1999). Measurements of resting potential indicate that neural stem cells maintain resting potentials in the -55 mV range (Wang et al, 2003). Since neural stem cells tend to be more depolarized than mature quiescent neurons, Cav1.2 channels might partially open without depolarization stimulus (Wang et al, 2003;Westerlund et al, 2003 Luo et al, 2005;Wang et al, 2005).…”
Section: +mentioning
confidence: 99%